Population genetics and reproductive biology of blue swimming crab, Portunus pelagicus (Linnaeus, 1758) in the west coast of Peninsular Malaysia - Sukimin, Intan Rohayu (2017)
Portunus pelagicus is an important commercial species that widely spread in the Peninsular Malaysia. This species attain high demand in the market due to their delicacy. The aims of this study were to determine the genetic diversityof P. pelagicus between two study areas using sequences of cytochrome c oxidase I (COI) mitochondrial DNA (mtDNA) gene, sexual maturity and reproduction pattern of P. pelagicus in Batu Pahat, Johor and Teluk kemang, Port Dickson. The specimens of P. pelagicus were collected monthly started from September 2015 to August 2016. All samples were measured their carapace width (CW), carapace length (CL) and body weight (BW) while maturity stages of male and female crabs were observed morphologically. The muscle tissues were taken for molecular analysis. Genetic diversity of two populations were determined through the haplotype and nucleotide diversity. Overall, a total of 63 sequences (599 bp) were obtained with 6 mtDNA haplotypes were found. The sharing of haplotypes among populations and low pairwise genetic distances (Fst) (0.2- 1.9 %) among haplotypes suggested high gene flow among the two populations.A total of 402 P. pelagicus individuals were examined including 254 males and 148 female. The result indicated that the overall sex ratio of males to females was 1: 0.36. The ratio shows that the numbers of females were lower than males which may be due to migration. The annual mean variation of GSI showed continuous breeding with the existence of four spawning peaks of different month (November, February, May and July) between September 2015 and August 2016 of the study area. The maximum GSI value 8.92 ± 5.096 was observed in the month of November 2015. While the minimum GSI value was 2.02 ± 1.918 observed in April 2016. The condition factors showed highest peak for male was 1.06 in August and female was 1.05 in May. The estimated mean size of males and female reached sexually matured (Lm50) at 112.56 mm and 114.21 mm CW respectively and show slightly different with some estimates in some other coastal waters of Malaysia, Indonesia and Philippines. This discrepancy might reflect of disparate in biology of the species and genetic composition. The estimated mean fecundity of P. pelagicus was 719,307 (range, 512269- 1524990) eggs. The fecundity of P. pelagicus was positively and linearly correlated with CW and CL and BW, so larger females produced high number of eggs than smaller ones because larger females have large body cavities. The high genetic similarities of the COI mtDNA analyses of P. pelagicus from Port Dickson and Batu Pahat obtained in this study concluded that this species belong to a same gene pool and be regarded as a single broodstock population. For sustainable use of crab at Teluk Kemang and Batu Pahat coastal waters, it is important to recommend a legal size and closure season based on spawning season and size at 50 % of sexual maturity. Thus, it is recommended the legal size of crab should be greater than 112.56 mm-CW for male and 114.21 mm-CW for female, while the closing season should be in November, February, May and July.